Rice-fish-duck system regulation of soil phosphorus fraction conversion and availability through organic carbon and phosphatase activity - Wang, Chao; Yang, Qiannan; Zhang, Chi; Li, Xiangdong; Chen, Jing; Zhang, Xiaolong; Chen, Jinjie; Liu, Kexue (Frontiers in Environmental Science, 2022)
Integrated ecological farming combines rice growing with aquaculture, and is an effective way to improve soil productivity by increasing soil nutrient supply. However, the long-term effects of such integrated farming on phosphorus fractions and phosphorus availability of paddy soils in the Pearl River Delta (PRD) remain unknown. A four-year field experiment compared the phosphorus fractions with paddy field in rice-fish-duck system (RFD), rice-vegetable cropping system (RVS) and conventional rice system (CRS) in the PRD. SOC and phosphorus fractions were significantly influenced by cropping systems. RFD significantly increased SOC and phosphorus in the soil. Soil phosphorus was dominated by moderately labile P (40.67–49.41%). RFD also significantly increased soil microbial biomass carbon, microbial biomass phosphorus, and acid phosphatase activity (ACP) by 67.68, 46.68, and 15.87% compared to RVS, and by 134.14, 65.99, and 30.20% compared to CRS, respectively. SOC and ACP were the primary factors influencing the conversion and effectiveness of soil phosphorus. The RFD can alleviate low phosphorus activity in PRD paddy soils through the combined effect of chemical and biological process, while promoting a sustainable soil nutrient cycle within the ecosystem and guiding the sustainable development of rational soil fertilization in the PRD.